AN APPROACH TO ELEMENTARY ACCOUNTING. - Beckert, Ralph F.; Reininga, Warren (The Accounting Review, 1965)
Abstract Many accounting professors complain that too much emphasis is placed on the mechanics and techniques in the elementary course. The mechanics have been reduced appreciably in many of the more popular textbooks being used today, but one still require the student to learn debit and credit technique. The debit and credit methodology is introduced very early in the course, usually in the first or second chapter, and from then on many of the illustrations rely solely on this technique to disclose or display both the "why" and "how" of a concept. This reliance on a record-keeping technique leads to an in-adequate understanding of the underlying principles and concepts in the elementary course. The emphasis is on an answer which is expressed as a debit and credit entry. Students and teachers alike fall a victim to this and use the mechanics as a "crutch". There is nothing basically wrong with teaching debit and credit technique. Every major should be thoroughly familiar with all the mechanics, and more, that are traditionally found in the beginning course.